2018
DOI: 10.1007/s10047-018-1057-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of regional saturation of oxygen monitor using near-infrared spectroscopy for lower limb ischemia during minimally invasive cardiac surgery

Abstract: Lower limb ischemia with an occlusive cannula is a potential complication of minimally invasive cardiac surgery (MICS). We evaluated intraoperative local oxygen supply-demand balance by monitoring regional saturation of oxygen (rSO) using near-infrared spectroscopy (NIRS), and analyzed the correlation between cannula size and fluctuation range of rSO. Fifty-four patients undergoing MICS surgery using femoral artery cannulation from April 2015 to August 2016 were enrolled. The rSO of both the cannulated and unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…Size discrepancy between the arterial cannula and the femoral artery is a suspected risk factor for lower limb ischemia. 8 , 14) A correlation between the cannula size relative to the femoral artery diameter and distal femoral artery flow velocity was observed in the present study, but the correlation was weak. From our results, we considered there were other factors determining the blood flow below cannulation site.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…Size discrepancy between the arterial cannula and the femoral artery is a suspected risk factor for lower limb ischemia. 8 , 14) A correlation between the cannula size relative to the femoral artery diameter and distal femoral artery flow velocity was observed in the present study, but the correlation was weak. From our results, we considered there were other factors determining the blood flow below cannulation site.…”
Section: Discussionsupporting
confidence: 42%
“…One of the methods used to monitor oxygenation in the lower leg is NIRS; this monitoring minimizes the risks associated with peripheral cannulation during MICS. 8) Inadequate perfusion to the lower extremity can develop during femoral arterial cannulation, and may result from decreased blood flow owing to insertion of the arterial cannula, displacement of the cannula, temporary obstruction through kinking, embolic events, or arterial spasm. Using NIRS to continuously monitor blood flow, poor oxygenation due to inadequate perfusion can be treated immediately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shirakawa et al [9] constructed 3D models of six prolapsed mitral valves for surgical assessment, and evaluated how accurately the models could replicate individual valve dimensions, to determining the complex geometry of mitral valve prolapse. They concluded that the 3D valve models could replicate the actual mitral valve prolapses within acceptable dimensional differences, and are useful for better 3D valve creation and better surgical planning with reliable 3D valve models.…”
Section: Cardiopulmonary Bypassmentioning
confidence: 99%
“…6,8 To our knowledge, there are only three English articles about the clinical use of NIRS to monitor leg ischemia during MICS. [9][10][11] We had introduced the NIRS monitoring system for distal leg ischemia during MICS in 2013 and established the criteria for initiation of distal perfusion cannulas to distal legs.…”
Section: Introductionmentioning
confidence: 99%